Lignicolous freshwater fungi along a north–south latitudinal gradient in the Asian/Australian region; can we predict the impact of global warming on biodiversity and function? - Hyde, Kevin D.; Fryar, Sally; Tian, Qing; Bahkali, Ali H.; Xu, Jianchu (Fungal ecology, 2016)
Fungi play a key role in decomposition of submerged wood in streams, breaking down lignocelluloses and releasing nutrients, and are important in ecosystem functioning. These wood decay fungi are known as freshwater lignicolous fungi and are usually studied by collecting submerged woody litter, followed by incubation in a moist chamber. This review explains what are freshwater lignicolous fungi, their decay mechanisms, roles and physiological attributes. Asian/Australasian lignicolous freshwater fungi have been relatively well-surveyed and enable an account of their distribution along a latitudinal transect. Unlike freshwater leaf-dwelling fungi their diversity in water bodies is greater towards the Equator which suggests they are important for decaying submerged wood in the tropics. Riparian vegetation, disturbances such as pollution, streams drying and study methods, may all affect the diversity of freshwater lignicolous fungi, however, the overall trend is a higher diversity in the tropics and subtropics. Climate changes together with increasing deposition of woody debris from human activities, and alteration of environmental factors (such as water pollution, and dam building) will impact freshwater lignicolous fungi. Changing diversity, structure and activities of freshwater fungal communities can be expected, which will significantly impact on aquatic ecosystems, particularly on nutrient and carbon cycles. There is a great opportunity to monitor changes in freshwater fungi communities along latitudinal (north to south) and habitat gradients (from human disturbed to natural habitats), and study ecological thresholds and consequences of such changes, particularly its feedback on nutrient and carbon cycles in freshwater systems.